Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

[tex]B=(\frac{-3}{16} x^{2} y) . (4x^{4}y^{3})[/tex]

Sagot :

Answer:

[tex]B=-\frac{3}{4}x^6y^4[/tex]

Step-by-step explanation:

One is given the following equation:

[tex]B=(\frac{-3}{16}x^2y)(4x^4y^3)[/tex]

Multiply each term in one of the parenthesis by its like term in the other. Bear in mind, since all of the operations in this equation are multiplication, one doesn't have to multiply every single term by another in the parenthesis, one only has to multiply like terms to simplify.

[tex]B=(\frac{-3}{16}x^2y)(4x^4y^3)[/tex]

[tex]B=(\frac{-3}{16})(4)(x^2)(x^4)(y)(y^3)[/tex]

Simplify further, remember, when multiplying two terms with the same base, one can add their exponents to simplify,

[tex]B=(\frac{-3}{16})(4)(x^2)(x^4)(y)(y^3)[/tex]

[tex]B=(\frac{-3*4}{16})(x^2^+^4)(y^1^+^3)[/tex]

[tex]B=(\frac{-3*4}{16})(x^6)(y^4)[/tex]

Now simplify the fraction, remove like terms found in both the numerator and denominator. Remember, (4) is a factor of both (4) and (16):

[tex]B=(\frac{-3*4}{16})(x^6)(y^4)[/tex]

[tex]B=(-\frac{3}{4})(x^6)(y^4)[/tex]

[tex]B=-\frac{3}{4}x^6y^4[/tex]